Hydrogen permeation through dense BaCe0.8Y0.2O3−δ – Ce0.8Y0.2O2−δ composite-ceramic hydrogen separation membranes. (30th January 2016) - Rosensteel, Wade A.; Ricote, Sandrine; Sullivan, Neal P.
Abstract: This report quantifies hydrogen permeation through dense 50/50 wt.-% BaCe0.8 Y0.2 O3− δ – Ce0.8 Y0.2 O2− δ membranes in which BaCe0.8 Y0.2 O3− δ serves as a proton conductor and Ce0.8 Y0.2 O2− δ serves as an electron conductor. A maximum hydrogen flux of 0.0744 mL cm −2 min −1 (5.54 × 10 −4 mol m −2 s −1 ) at 900° C is observed through a 1.44-mm-thick membrane with a 0.5 atm hydrogen partial pressure gradient. This results in a permeability of 0.0107 mL cm −1 min −1 when normalized by thickness. This is one of the highest permeabilities reported to date for proton-conducting ceramic membranes. While permeation rates through BaCe0.8 Y0.2 O3− δ – Ce0.8 Y0.2 O2− δ membranes are promising, membrane performance is found to degrade over time. The source of degradation is hypothesized to be the formation of a dopant–deficient phase on the feed-side membrane surface which creates an increased inter-granular contact resistance. Additionally, Ni metal particles are observed inside of internal pores, and at grain boundaries between BaCe0.8 Y0.2 O3− δ and Ce0.8 Y0.2 O2− δ grains, indicating the reduction of the NiO used in solid-state reactive sintering during device operation. These particles may contribute to increased mechanical stresses between grains and subsequent membrane fracture. While the permeation demonstrated by these composite membranes is encouraging, further development is needed before these novel materials can be used in commercial applications. Highlights: A novel composite-ceramic hydrogen-separation membrane is presented. BaCe0.8 Y0.2 O3−d – Ce0.8 Y0.2 O2−d (BCY–YDC) composite membrane. BCY serving as proton conductor and YDC as electron conductor. Materials synthesis and membrane fabrication are combined into a single processing step. Hydrogen permeability is the second highest ever reported for ceramic-based membranes.